Heterogeneity in the rebound effect: Further evidence for Germany - Manuel Frondel; Nolan Ritter; Colin Vance (Energy Economics, 2012)
Rebound effects measure the behaviorally induced offset in the reduction of energy consumption following efficiency improvements. Using both panel estimation and quantile regression methods on household travel diary data collected in Germany between 1997 and 2009, this study investigates the heterogeneity of the rebound effect in private transport. With the average rebound effect being in the range of 57% to 62%, our results are in line with a recent German study by Frondel, Peters, and Vance (2008), but are substantially larger than those obtained from other studies. Furthermore, our quantile regression results indicate that the magnitude of estimated fuel price elasticities – from which rebound effects can be derived – depends inversely on the household's driving intensity: households with low vehicle mileage exhibit fuel price elasticities, and hence rebound effects, that are significantly larger than those for households with high vehicle mileage.
Keywords: 330; Automobile travel; Panel models; Quantile regression